2009
DOI: 10.1017/s0714980809990195
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Awareness of Community Health and Support Services for Dementia Care

Abstract: RÉSUMÉL’article examine où les personne agées peuvent chercher l’aide pour prendre soin d’un parent avec démence et les facteurs associés à leur identification des services de santé et de soutien communautaires comme des sources d’aide. Les auteurs menées des entrevues téléphoniques, à l’aide de numérotation de chiffres aléatoires, de 1,152 adultes âgés de 50 et plus dans la ville de Hamilton. À déterminer les sources de soutien, plus 37 pour cent des répondants a identifié leur médecin, 33 pour cent a identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 39 publications
1
59
1
Order By: Relevance
“…However, Ploeg et al [51] suggest that people often do not know where to turn for information on services, relying mainly upon their General Practitioner (GP) or primary care physician.…”
Section: Resultsmentioning
confidence: 99%
“…However, Ploeg et al [51] suggest that people often do not know where to turn for information on services, relying mainly upon their General Practitioner (GP) or primary care physician.…”
Section: Resultsmentioning
confidence: 99%
“…32 Streams et al 39 presented their caregiver participants with a list of 19 triggers, such as patient changes, asking them whether and from whom they would seek help for each trigger. Six studies developed self-report questions specifically for the study.…”
Section: Hs Assessmentmentioning
confidence: 99%
“…Ploeg et al . (), investigating dementia caregivers’ identification of support services, showed that the majority identified their physician and only 33% identified informal support such as family and neighbours. Understanding the complex nature and quality of the relationships adds insight as to how they may influence provision of care and the personhood of individuals with dementia (Smebye & Kirkevold ).…”
Section: Discussionmentioning
confidence: 99%